Understanding the I ching : the Wilhelm lectures on the Book of Changes - Wilhelm, Hellmut; Wilhelm, Richard (Princeton, N.J. : Princeton University Press, 1995)
The West's foremost translator of the I Ching, Richard Wilhelm thought deeply about how contemporary readers could benefit from this ancient work and its perennially valid insights into change and chance. For him and for his son, Hellmut Wilhelm, the Book of Changes represented not just a mysterious book of oracles or a notable source of the Taoist and Confucian philosophies. In their hands, it emerges, as it did for C. G. Jung, as a vital key to humanity's age-old collective unconscious. Here the observations of the Wilhelms are combined in a volume that will reward specialists and aficionados with its treatment of historical context - and that will serve also as an introduction to the I Ching and the meaning of its famous hexagrams.
Change: Eight Lectures on the I Ching. 1. Origins. 2. The Concept of Change. 3. The Two Fundamental Principles. 4. The Trigrams and the Hexagrams. 5. The Hexagrams Ch'ien and K'un. 6. The Ten Wings. 7. The Later History of the Book of Changes. 8. The Oracle Book -- Lectures on the I Ching: Constancy and Change. Opposition and Fellowship. The Spirit of Art According to the Book of Changes. Constancy in Change. Death and Renewal.
Izvorno objavljeno kao: Change : eight lectures on the I ching / by Hellmut Wilhelm ; translated from the German by Cary F. Baynes (Bollingen Series LXII) i: Lectures on the I ching : constancy and change / by Richard Wilhelm ; translated from the German by Irene Eber (Bollingen Series XIX:2). New York : Bollingen Foundation, cop. 1960
Bibliografija: str. [317]-325 i kazalo
Keywords: Yi jing - tumačenje -- Knjiga promjena - tumačenje -- kineska religija -- taoizam -- kineska filozofija